Total Versus Near-total Thyroidectomy in Graves Disease: Results of the Randomized Controlled Multicenter TONIG-trial. Issue 5 (November 2019) - Maurer, Elisabeth; Maschuw, Katja; Reuss, Alexander; Zieren, Hans Udo; Zielke, Andreas; Goretzki, Peter; Simon, Dietmar; Dotzenrath, Cornelia; Steinmüller, Thomas; Jähne, Joachim; Kemen, Matthias; Coerper, Stephan; et al.
Abstract : Background: Previous data suggest that the incidence of hypoparathyroidism after surgery for Graves disease (GD) is lower after subtotal thyroidectomy compared to total thyroidectomy (TT). The present study evaluated the incidence of postoperative hypoparathyroidism after near-total (NTT) versus TT in GD. Methods/Design: In a multicenter prospective randomized controlled clinical trial, patients with GD were randomized intraoperatively to NTT or TT. Primary endpoint was the incidence of transient postoperative hypoparathyroidism. Secondary endpoints were permanent hypoparathyroidism, transient recurrent laryngeal nerve palsy (RLNP), reoperations for bleeding, inadvertently removed parathyroid glands, and recurrent hyperthyroidism after 12 months. Results: Eighteen centers randomized 205 patients to either TT (n = 102) or NTT (n = 103) within 16 months. According to intention-to-treat postoperative transient hypoparathyroidism occurred in 19% (20/103) patients after NTT and in 21% (21 of 102) patients after TT ( P = 0.84), which persisted >6 months in 2% and 5% of the NTT and TT groups ( P = 0.34). The rates of parathyroid autotransplantation (NTT 24% vs TT 28%, P = 0.50) and transient RLNP (NTT 3% vs TT 4%, P = 0.35) was similar in both groups. The rate of reoperations for bleeding tended to be higher in the NTT group (3% vs 0%, P = 0.07) and the rate of inadvertently removed parathyroid glands was significantly higher after NTT (13% vs 3%, P = 0.01). An existing endocrine orbitopathy improved in 35% and 24% after NTT and TT ( P = 0.61). Recurrent disease occurred in only 1 patient after TT ( P = 0.34). Conclusion: NTT for GD is not superior to TT regarding transient postoperative hypoparathyroidism. Abstract : Supplemental Digital Content is available in the text